Genome-based study of a spatio-temporal cluster of invasive meningococcal disease due to Neisseria meningitidis serogroup C, clonal complex 11. Issue 2 (August 2016) - Stefanelli, P.; Fazio, C.; Neri, A.; Ciammaruconi, A.; Balocchini, E.; Anselmo, A.; Azzari, C.; Rossolini, G.M.; Vacca, P.; Fortunato, A.; Palozzi, A.; Fillo, S.; et al.
Summary: Objectives: To describe a spatio-temporal cluster of invasive meningococcal disease (IMD) due to serogroup C meningococci, occurred in a restricted area of Tuscany between January and October 2015, and the results of whole genome sequencing (WGS). Methods: Surveillance activities and public health measures were implemented in the Region. Bacterial isolates from IMD cases were characterized by the National Reference Laboratory of the Istituto Superiore di Sanità (ISS), and WGS was performed on available strains. The kSNP software was used to identify core genome SNPs. Results: Overall, 28 IMD cases due to meningococcus C were identified up to 31st October, 2015. Of them, 26 were due to meningococcus C:P1.5-1, 10-8: F3-6:ST-11 (cc11) and 2 to C:P1.5-1, 10-8: F3-6:ST-2780 (cc11). WGS of 13 meningococci isolated during the outbreak occurred in Tuscany in 2015 showed higher similarity when compared with those of 47 C: P1.5-1, 10-8: F3-6:ST-11 (cc11) invasive strains from sporadic cases previously detected in Italy. Conclusions: A highly aggressive meningococcal C strain was involved in the cluster of severe IMD occurred in Tuscany, a Region with high vaccine coverage among children. Whether this was due to low herd immunity related to the short duration of vaccine protection needs further investigation.